2013
DOI: 10.3402/ljm.v8i0.20185
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of metabolic syndrome components, individually and in combination, in male patients admitted with acute coronary syndrome, without previous diagnosis of diabetes mellitus

Abstract: BackgroundMortality from cardiovascular disease in the Middle East is projected to increase substantially in the coming decades. The prevalence of metabolic syndrome (MS) in acute coronary syndrome (ACS) continues to raise interest, but data from the Middle East is limited, especially in non-diabetic patients. This study was conducted to ascertain the prevalence of MS and frequency of its components, individually and in combination, in a male population presenting with ACS, but without a previous diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
3
11
1
1
Order By: Relevance
“…This conclusion is consistent with a previous report, where increasing age was found to affect the prevalence of MetS [14]. Individuals with lower income showed increased risk of MetS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This conclusion is consistent with a previous report, where increasing age was found to affect the prevalence of MetS [14]. Individuals with lower income showed increased risk of MetS.…”
Section: Discussionsupporting
confidence: 93%
“…In the literature the prevalence of different components varied considerably with some components being the most prevalent in some studies and least prevalent in other studies [14,15]. The high prevalence rate of central obesity in this study is consistent with the reported increasing rate in the literature [16].…”
Section: Discussionsupporting
confidence: 86%
“…In patients hospitalized for ACS, the prevalence ranged between 43% and [19]. Recently, Al-Aqeedi et al [20] reported that in ACS patients without history of diabetes MS was frequent (69.4%) and reduced HDL increased fasting blood glucose, and triglycerides were the most frequent MS components. Although MS is frequently associated with diabetes, in the absence of diabetes MS resulted in increased cardiovascular events and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were diagnosed according to diagnostic criteria for MS of the Chinese Diabetes Society in 2004 and were assigned to the MS group if they satisfied three or four of the following conditions (Al-Aqeedi et al, 2013;Cavali Mde et al, 2010): obesity, body mass index (BMI) of 25.0 kg/m 2 or greater; hyperglycemia or diabetes mellitus, fasting plasma glucose of 6.1 mmol/l or greater or plasma glucose of 7.8 mmol/l or greater; hypertension, systolic/diastolic pressure of 140/90 mm Hg or greater; and dyslipidemia, fasting serum triglycerides (TGs) of 1.7 mmol/l or greater or fasting high-density lipoprotein cholesterol (HDL-C) of less than 0.9 mmol/l for the men and less than 1.0 mmol/l for the women.…”
Section: Patientsmentioning
confidence: 99%